2021
DOI: 10.2298/jmmb200403009c
|View full text |Cite
|
Sign up to set email alerts
|

Nodule count effect on microstructure and mechanical properties of hypo-eutectic ADI alloyed with nickel

Abstract: Samples of ductile iron alloyed with 0.88 % Ni with a nodule count of 606, 523, and 290 nod/mm2 were obtained from sand cast plates of different thickness in the range from 8.46 to 25.4 mm. The effect of the nodule count was evaluated during the austempering process held at 285?C and austempering times of 15, 30, 45, 60, 70, and 90 min. The volume fraction of high carbon austenite was increased when the nodule count was increased, however, the carbon content of the high carbon austenite kept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(40 reference statements)
1
6
0
Order By: Relevance
“…Figure 11 shows the hardness evolution as the austempering time was increased. The hardness behavior is directly related to the microstructural evolution shown in Figures 4 and 5 and also with the %Vγ HC as was previously reported [38,45].…”
Section: Mechanical Propertiessupporting
confidence: 81%
See 3 more Smart Citations
“…Figure 11 shows the hardness evolution as the austempering time was increased. The hardness behavior is directly related to the microstructural evolution shown in Figures 4 and 5 and also with the %Vγ HC as was previously reported [38,45].…”
Section: Mechanical Propertiessupporting
confidence: 81%
“…The maximum value of %Vγ HC in all cases was obtained for the austempering time of 90 min. The maximum ausferrite amount referred to as a process window (PW) and represented in Equations ( 1)-( 3) occurs as follows: The first stage of the PW is presented to the austempering times of 30 and 60 min where Reaction (1) proceeds; afterwards, the highest amount of ausferrite is obtained at 90 min, reaching the PW (reaction 3), and then, the second stage of the PW window has been reached at the austempering time of 120 min, proceeding Reaction (2) [38]. It is observed from Table 4 that the highest values of %Vγ HC are reached for the highest austempering temperature; this behavior is related to the carbides amount in the ausferritic matrix [39].…”
Section: Volume Fraction Of High-carbon Austenitementioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned that austemperability enhancement is resulted from the segregation reduction, which means more uniform distribution of elements concentration. In addition, it was reported that 19,20 increasing the nodule count extremely refines the ausferrite structure in the matrix. Consequently, this leads to improve both strength and ductility of the produced ADI parts.…”
Section: Introductionmentioning
confidence: 99%